"The coupons and stuff just made it possible": economic constraints and patient experiences of a produce prescription program. Issue 5 (30th September 2019) - Schlosser, Allison V; Joshi, Kakul; Smith, Samantha; Thornton, Anna; Bolen, Shari D; Trapl, Erika S
Abstract : Patients with hypertension who also experience food insecurity experience economic barriers to participating in a produce prescription program even after vouchers for produce were provided. Abstract: Although produce prescription (PRx) programs have been shown to improve fruit and vegetable (FV) consumption, few studies have examined how economic constraints influence participant experience. We conducted a qualitative study of patient experience of a 3-month PRx program for hypertension (PRxHTN) including 3 safety-net clinics and 20 farmers' markets (FMs). We interviewed 23 PRxHTN participants using semistructured guides to understand their program experiences. Interviews were audio-taped, transcribed, and analyzed to identify a priori and emergent themes. PRxHTN participants completing qualitative interviews were mostly middle-aged (mean: 62 years) African American (100%) women (78%). Economic hardship as a barrier to maximum program participation and sustainability was a main theme identified, with three subthemes: (i) transportation issues shaped shopping and eating patterns and limited participant ability to access FMs to utilize PRxHTN vouchers; (ii) limited and unstable income shaped participant shopping and eating behavior before, during, and after PRxHTN; and (iii) participants emphasized individual-level influences like personal or perceived motivations for program participation, despite significant structural constraints, such as economic hardship, shaping their program engagement. Future PRx programs should bolster economic and institutional supports beyond FM vouchers such as transportation assistance, partnering with local food banks and expansion to local grocery stores offering year-round FV access to support sustained behavior change. Additionally, structural competency tools for providers may be warranted to reorient focus on structural influences on program engagement and away from potentially stigmatizing individual-level explanations for program success. These efforts have potential to enhance the translation of PRx programs to the needs of economically vulnerable patients who struggle to manage chronic illness and access basic nutrition.